Ethical Contracting for Clinical Trials - Binik-Thomas, Justin (Journal of Accounting and Finance, 2023)
The manuscript explores types of contractual review and ethics related to mutual terms as visualized by the Bowtie Risk Assessment. The researcher proposed two ethical crosscheck methods for clinical trials (1) the Four Way Test and (2) the Virtuous Model. Protecting each organization’s interests through bilateral terminology is always appropriate as it is ethical and builds goodwill and camaraderie. When conducting these reviews and considerations through an ethical lens, the legal and financial risks related to unknown factors — force majeure occurrences, out-of-scope needs, unexpected changes, and regulatory issuances — also reduce. Through an ethical lens, the review benefits from working to resolve in good faith and towards a commonality.